2021
DOI: 10.3389/fvets.2021.764135
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Mammary Metabolic Changes in Dairy Cows Exposed to Hypoxia

Abstract: Hypoxia exposure can cause a series of physiological and biochemical reactions in the organism and cells. Our previous studies found the milk fat rate increased significantly in hypoxic dairy cows, however, its specific metabolic mechanism is unclear. In this experiment, we explored and verified the mechanism of hypoxia adaptation based on the apparent and omics results of animal experiments and in vitro cell model. The results revealed that hypoxia exposure was associated with the elevation of AGPAT2-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Glucose metabolism and pyruvate metabolism are the main ways for brain cells to produce energy [56]. And glycerophospholipid metabolism contributes to hypoxia adaptation [57]. Our study found that BRP can drive metabolites (pyruvate, psychosine, sphingosine-1-phosphate, sphingosine, myristoylcarnitine, LysoPE (16 : 1(9Z)/0 : 0), and LysoPA (16 : 0/0 : 0)) to normal levels by regulating pyruvate metabolism, glycolysis/gluconeogenesis, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism and pyruvate metabolism are the main ways for brain cells to produce energy [56]. And glycerophospholipid metabolism contributes to hypoxia adaptation [57]. Our study found that BRP can drive metabolites (pyruvate, psychosine, sphingosine-1-phosphate, sphingosine, myristoylcarnitine, LysoPE (16 : 1(9Z)/0 : 0), and LysoPA (16 : 0/0 : 0)) to normal levels by regulating pyruvate metabolism, glycolysis/gluconeogenesis, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ten dairy cows were regarded as the control group (Con) with SCC less than 5 × 104 cells/mL, and the other ten dairy cows were regarded as the mastitis group (Mas), with SCC greater than 5 × 106 cells /mL. The basal diet (shown in Table 1) [17] was formulated to meet the nutrient requirements for energy, protein, minerals, and vitamins according to the Feeding Standards of Dairy Cattle in China [18]. All dairy cows were fed the same total mixed ration (TMR) diets ad libitum.…”
Section: Animals and Experimental Designmentioning
confidence: 99%